Halide Perovskites: Kilogram‐Scale Crystallogenesis of Halide Perovskites for Gamma‐Rays Dose Rate Measurements (Adv. Sci. 2/2021). Issue 2 (20th January 2021) - Andričević, Pavao; Frajtag, Pavel; Lamirand, Vincent Pierre; Pautz, Andreas; Kollár, Márton; Náfrádi, Bálint; Sienkiewicz, Andrzej; Garma, Tonko; Forró, László; Horváth, Endre
Abstract : In article number 2001882, Pavao Andričević, László Forró, and co‐workers introduce the 'oriented crystal‒crystal intergrowth' method, yielding solution‐grown MAPbBr3 crystals with volume and mass of over 1000 cm 3 and 3 kg. Its increased size, equipped with carbon electrodes, is utilized for sensitive gamma ray detection of a 60 Co source at the dose rate up to 2.3 Gy h −1 at ambient conditions.